2014
DOI: 10.1186/1746-6148-10-20
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphisms within the Telomerase Reverse Transcriptase gene (TERT) in four breeds of dogs selected for difference in lifespan and cancer susceptibility

Abstract: BackgroundEnzymatic activity of Telomerase Reverse Transcriptase (TERT) is important in maintaining the telomere length and has been implicated in cancer and aging related pathology. Since cancer susceptibility as well as longevity of dogs vary between breeds, this study involved sequencing the entire TERT gene of Canis familiaris from DNA samples obtained from forty dogs, with ten dogs each of four breeds: Shih Tzu, Dachshund, Irish Wolfhound, and Newfoundland, each with different life expectancies and suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…In canines, susceptibility to cancer is thought to vary between breeds [57]. Regardless of the type of cancer, an evaluation of the immunological status of tumor-bearing dogs showed that such tumor-bearing dogs had higher numbers of leukocytes than normal dogs [58].…”
Section: Cancermentioning
confidence: 99%
“…In canines, susceptibility to cancer is thought to vary between breeds [57]. Regardless of the type of cancer, an evaluation of the immunological status of tumor-bearing dogs showed that such tumor-bearing dogs had higher numbers of leukocytes than normal dogs [58].…”
Section: Cancermentioning
confidence: 99%
“…In addition, the study of telomerase must be extended to a broader range of species in non-models animals like birds, fish, mammals or insects, where descriptive studies on change in telomerase activity with age or tissue have already paved our way (e.g. (Hartmann et al, 2009;Jemielity et al, 2007;Koubová et al, 2019;McAloney, Silverstein, Modiano, & Bagchi, 2014;O'Hare & Delany, 2005;Wang, McAllan, & He, 2011). Adding original data on, more particularly, the pleiotropic action of canonical and non-canonical activities of telomerase, and exploring how they may have co-evolved with particular life-history traits form our next scientific objective.…”
Section: Conclusion: There Is a Lot To Gain In Studying Telomerase Fo...mentioning
confidence: 99%
“…Of course, heterozygotes of mutated genes ( TERT −/+ or TERC −/+) will be more valuable as they will take us beyond the on/off (i.e., sterile/fertile) phenotypes. In addition, the study of telomerase must be extended to a broader range of species in non‐models animals such as birds, fish, mammals or insects, where descriptive studies on change in TA with age or tissue have already paved our way (e.g., Hartmann et al, 2009 ; Jemielity et al, 2007 ; Koubová et al, 2019 ; McAloney et al, 2014 ; O'Hare & Delany, 2005 ; Wang et al, 2011 ). Measurement of TA in such studies should be a natural next step via the use of already available and easily adaptable methods (e.g., TRAP assays, Mensà et al, 2019 ).…”
Section: Conclusion: There Is a Lot To Gain In Studying Telomerase Fo...mentioning
confidence: 99%
“…Також встановлено, що можливе успадкування більш довгих теломер завдяки подовженню теломер у сперматозоїдів, що у свою чергу уповільнить процеси старіння [11], а отже може відобразитись на продуктивній придатності тварин. Крім, того зміни у регуляції та у самому гені TERT призводять до більшої схильності до захворювань [12]…”
unclassified